Symptoms and transmission of intestinal cryptosporidiosis. Issue 4 (April 1990) - Egger, M; Mäusezahl, D; Odermatt, P; Marti, H P; Tanner, M
Abstract : Cryptosporidium spp are a cause of diarrhoea in toddlers. Symptoms and routes of transmission were investigated in a prospective case-control study in the city and surroundings of Basel, Switzerland. Twenty one (4.6%) out of 455 children with diarrhoea who attended paediatric and general practices from June to September 1988 were positive for cryptosporidium. The mothers of each case, of two controls with diarrhoea of another origin, and of two healthy controls were interviewed with a standardised questionnaire. In comparison with controls with diarrhoea of another origin, respiratory symptoms were significantly more frequent in children with cryptosporidiosis: eight of 19 (42%) compared with five of 38 (13%). In comparison with healthy controls, preceding contact with a person suffering from diarrhoea was associated with the greatest relative risk for cryptosporidiosis, followed by travel in a Mediterranean country. Transient cryptosporidial infection of the respiratory tract may be common in immunocompetent children. In the area investigated person to person transmission may account for most cases.